The importance of foreign language skills in the tourism sector: a study of employees’ perceptions in hotels in Malaysia - Selke, Raimond (2013)
Promoting tourism is a crucial part of the national economic policy in Malaysia and thus there is an inherent need to attract and cater for more than 25 million overseas visitors. Malaysia is a multi-ethnic and multi-linguistic country. Malaysia has a good reputation among overseas visitors for being safe, for an abundance of, and a great diversity of, cultural and touristic sites. Among the four actively spoken languages in Malaysia: Bahasa Malaysia, Chinese, Tamil and English, English is the established “lingua franca” of international communication, trade, business and media. English has an important role to play in the delivery of quality service in the hospitality industry. Hotels are the largest sector in the hospitality industry. However, an examination of the literature of hotels in Malaysia, especially in regard to the front-of-house services offered within them, reveals a lack of conclusions as to the perceptions of employees on the use and need of foreign languages. The front-of-house services are of particular interest as they have the most guest contact (Wagen, 2003). There is very little data concerning how various hotel staffs perform in guest communication. This study looks at communication in hotels, using quantitative and qualitative data to discover what perceptions hotel employees hold, as seen as a group, and what hotel division managers, as seen as a group, hold on the importance of various languages. English is the most important language for guest communication. But in our project, we will look beyond English. We analyze the role of other foreign languages as well. English is, of course, considered the second language of Malaysia after the national language, Bahasa Malaysia. Questionnaire surveys are being, and will be, used to collect data from more than 200 front-of-house staff and at least 50 division managers. Additional data will be gathered from semi-structured interviews of more than 20 managers and from more than 20 informal interviews with front-of-house staff. Fisher’s exact test will be employed to measure the gaps between the perceived needs and performance, staff versus management, and department versus department. The data will be subjected to a constant comparative method of analysis. This research project is ongoing.